Relationship Between Knee Pain and Infrapatellar Fat Pad Morphology: A Within‐ and Between‐Person Analysis From the Osteoarthritis Initiative. Issue 4 (11th March 2018) - Steidle‐Kloc, Eva; Culvenor, Adam G.; Dörrenberg, Jan; Wirth, Wolfgang; Ruhdorfer, Anja; Eckstein, Felix
Abstract : Objective: Inflammation is known to be strongly associated with knee pain in osteoarthritis. The infrapatellar fat pad represents a potential source of proinflammatory cytokines. Yet the relationship between infrapatellar fat pad morphology and osteoarthritis symptoms is unclear. Methods: Here we investigate quantitative imaging parameters of infrapatellar fat pad morphology between painful versus contralateral pain‐free legs of subjects with unilateral knee pain and patients with chronic knee pain versus those of matched pain‐free control subjects. A total of 46 subjects with strictly unilateral frequent knee pain and bilateral radiographic osteoarthritis (Kellgren/Lawrence grade 2/3) were drawn from the Osteoarthritis Initiative. Further, 43 subjects with chronic knee pain over 4 years and 43 matched pain‐free controls without pain over this period were studied. Infrapatellar fat pad morphology (volume, surface area, and depth) was determined by manual segmentation of sagittal magnetic resonance images. Results: No significant differences in infrapatellar fat pad morphology were observed between painful versus painless knees of persons with strictly unilateral knee pain (mean difference −0.7% (95% confidence interval [95% CI] −0.6, 0.9; P = 0.64) or between chronically painful knees versus matched painless controls (−2.1% [95% CI −2.2, 1.1]; P = 0.51). Conclusion: Independent of the ambiguous role of the infrapatellar fat pad in knee osteoarthritis (a potential source of proinflammatory cytokines or a mechanical shock absorber), the size of the infrapatellar fat pad does not appear to be related to knee pain.